1991
DOI: 10.1164/ajrccm/143.6.1317
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Change in Bronchial Reactivity with an Inhaled Corticosteroid in Asthma

Abstract: The time course of change in FEV1, bronchial reactivity, and daily measures of asthma control (peak expiratory flow, symptoms, and beta 2-agonist inhaler use) was determined during 6 wk of treatment with inhaled budesonide, 800 micrograms twice a day, and for 2 wk following cessation of treatment in 40 asthmatic subjects in a double-blind, placebo-controlled, parallel group study. Histamine reactivity, expressed as the provocative dose of histamine causing a 20% fall in FEV1 (PD20), was measured at intervals d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 5 publications
2
77
1
1
Order By: Relevance
“…In the present study, airway reactivity and lung function remained stable in both groups of patients for 12 weeks after ICS withdrawal/reduction, although the placebo-treated patients were more symptomatic during this period, observations that are in keeping with the data of JUNIPER et al [18] and HAAHTELA et al [19]. In contrast, other investigators [20][21][22] have found that the beneficial effects of ICS, in terms of control of symptoms, lung function and airway reactivity, are not maintained after cessation of therapy. There is no single explanation for the conflicting results of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, airway reactivity and lung function remained stable in both groups of patients for 12 weeks after ICS withdrawal/reduction, although the placebo-treated patients were more symptomatic during this period, observations that are in keeping with the data of JUNIPER et al [18] and HAAHTELA et al [19]. In contrast, other investigators [20][21][22] have found that the beneficial effects of ICS, in terms of control of symptoms, lung function and airway reactivity, are not maintained after cessation of therapy. There is no single explanation for the conflicting results of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…day -1 [6,7,31,32], have reported improvements from baseline in morning PEF of 20±40 L . min -1 and in AHR of 1±2 doubling doses.…”
Section: Discussionmentioning
confidence: 97%
“…The magnitude of the reduction differs, but often airway responsiveness remains abnormally increased [50]. When therapy is discontinued, airway responsiveness usually returns to pretreatment levels [53][54][55].…”
Section: Anti-mediator Effectsmentioning
confidence: 99%